The Influence of Using Instagram's Social Media Account @Neohistoria.Id In Fulfilling Followers' Information Needs - Prayoga, Arya Aldin; Saktisyahputra (Sinergi International Journal of Communication Sciences, 2023)
Today the world has entered the era of globalization, various kinds of technology are growing very rapidly. The growth of technology is also based on human needs, humans have a need for information, on the development of technology, humans can easily access the information needed through the media. This information is of course obtained through mass media such as television, radio, magazines, films, newspapers, tabloids, and mass media, namely letters, telephones, posters, telegrams, banners and so on. One of the accounts that uses Instagram social media to spread information is Instagram @Neohistoria.id. This study uses quantitative methods. The author is interested in knowing the effect of using Instagram social media accounts on meeting information needs. The purpose of the study was to determine the effect of using the Instagram @Neohistoria.id social media account on meeting the information needs of followers and to find out how much influence social media had on meeting information needs. Data collection in this study is by distributing questionnaires to 100 respondents who were determined through accidental sampling. The data obtained were analyzed using validity tests, reliability tests, simple regression tests, correlation coefficients, coefficients of determination, and T tests. The results of this study obtained positive regression results, which means that there is effectiveness of social media in meeting information needs.